New Oral Anticoagulants: General Features and Review of Pivotal Clinical Trials - Sung-Won Jang (Yong Chan Lee, 2016)
For the last half century, vitamin K antagonists (VKAs) have been used for treatment and prevention of venous thromboembolism and stroke prevention in patients with atrial fibrillation. However, their fragile pharmacokinetics, need for routine laboratory monitoring and dose adjustments complicated the use of these drugs. Recently, new oral anticoagulants (NOACs) have overcome the limitation of VKA therapy and shows favorable outcomes and better safety, especially for patients with intracranial hemorrhage, both in phase III clinical trials and real-world registry. Currently available NOACs are one thrombin inhibitor, dabigatran, and three Xa inhibitors, rivaroxaban, apixaban, and edoxaban. This review covers the pharmacokinetics, published pivotal clinical trials, and dose adjustments in chronic kidney disease. The reimbursement criteria, discontinuation during elective surgical procedure, issues on reversal agents are also discussed.